Fragments of Fullerenes and Carbon Nanotubes : Designed Synthesis, Unusual Reactions, and Coordination Chemistry - Petrukhina , Marina A.; Scott, Lawrence T. (New Jersey : John Wiley, 2012)
This book is the first of its kind to reflect upon the intense and rapidly growing interest in open geodesic polyaromatic molecules, specifically focusing on their synthesis and reactivity in metal binding reactions. The book broadly covers all aspects related to the fullerene fragment chemistry: current synthetic techniques, description of the available members of this new family (which has grown to more than two dozens members, with none being available commercially), molecular geometry and trends in the solid state packing, as well as extensions into physical properties and new buckybowl-based molecules and materials. It covers fundamental research related to a new class of hydrocarbons, namely open geodesic polyarenes that map onto the surfaces of fullerenes (and referred to as fullerene fragments or buckybowls.
Includes bibliographical references; Index 401-413p.
Keywords: Carbon nanotubes; Fragments of fullerenes; Physics; Nano-science.